Incorporation of water in iron-free ringwoodite: A first-principles study - Blanchard, M.; Balan, E.; Wright, Kathleen (Mineralogical Society of America, 2009)
The structures, infrared active OH stretching modes, and relative energies of OH-defects in ringwoodite(?-Mg2SiO4) have been studied by first-principles calculations based on density functionaltheory (DFT). Two types of fully protonated cationic defects in normal spinel were considered at 0and 20 GPa, i.e., [VMg(OH)2]x, [VSiOH)4]x defects. In addition, two defects associated with the partialinversion of the spinel structure have been investigated. The first one corresponds to two protonscompensating a Mg substituted for Si in tetrahedral site, [MgSi(OH)2]x, whereas the second defectcorresponds to a Mg vacancy located nearby a Mg-Si substitution, [VMg(OH)2MgSiSiMg]x. The infraredspectrum and evolution with pressure of these OH-defects make it possible to interpret the major IRabsorption bands experimentally observed. The main absorption band at ~3150 cm?1 corresponds toprotons located between the O-O pairs shared by 16c and 16d octahedra, instead of OH along thetetrahedral edges as usually proposed in the literature. The large width of this band is most likelyrelated to the association of OH defects with the various cationic configurations related to the partialinversion of a vacancy-bearing spinel structure. The less intense band at ~3675 cm?1 is assigned tohydrogarnet-type defects with a protonation of the tetrahedral edges. This interpretation is consistentwith an Mg/Si ratio lower than 2 and its weak variation as a function of water concentration, as experimentally observed. These results emphasize the importance of taking into account the structuralrelaxation experienced by defects, instead of using empirical correlation, to assign OH stretchingbands to specific O-O pairs of the structure.